On the convergence of difference schemes for the diffusion equation of fractional order - Bechelova, A. R. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For the diffusion equation of fractional order, we construct an approximation difference scheme of order 0(h 2 + τ). We present an algorithm for the solution of boundary-value problems for a generalized transfer equation of fractional order.